TREM-1 Promotes Pancreatitis-Associated Intestinal Barrier Dysfunction - Shengchun Dang; Yao Shen; Kai Yin; Jianxin Zhang (Gastroenterology Research and Practice)
Severe acute pancreatitis (SAP) can cause intestinal barrier dysfunction (IBD), which significantly increases the disease severity and risk of mortality. We hypothesized that the innate immunity- and inflammatory-related protein-triggering receptor expressed on myeloid cells-1 (TREM-1) contributes to this complication of SAP. Thus, we investigated the effect of TREM-1 pathway modulation on a rat model of pancreatitis-associated IBD. In this study we sought to clarify the role of TREM-1 in the pathophysiology of intestinal barrier dysfunction in SAP. Specifically, we evaluated levels of serum TREM-1 and membrane-bound TREM-1 in the intestine and pancreas from an animal model of experimentally induced SAP. TREM-1 pathway blockade by LP17 treatment may suppress pancreatitis-associated IBD and ameliorate the damage to the intestinal mucosa barrier.